Islamic law and human rights : the Muslim Brotherhood in Egypt - Fegiery, Moataz El (Cambridge Scholars Publishing, 2016)
This book explores the development of the Muslim Brotherhood's thinking on Islamic law and human rights, and argues that the Muslim Brotherhood has exacerbated, rather than solved, tensions between the two in Egypt. The organisation and its scholars have drawn on hard-line juristic opinions and reinvented certain concepts from Islamic traditions in ways that limit the scope of various human rights, and advocate for Islamic alternatives to international human rights. The Muslim Brotherhood's practices in opposition and in power have been consistent with its literature. As an opposition party, i.